Mid‐term outcomes of simultaneous coronary artery bypass graft surgery and septal myectomy in patients with hypertrophic obstructive cardiomyopathy: A case‐controlled study. Issue 3 (12th January 2019) - Wang, Shengwei; Cui, Hao; Tang, Bing; Zhu, Changsheng; Meng, Liukun; Yu, Qinjun; Huang, Xiaohong; Wu, Rong; Wang, Shuiyun
Abstract: Background: The mid‐term outcome of patients with hypertrophic obstructive cardiomyopathy (HOCM) undergoing coronary artery bypass graft (CABG) is unclear. Materials and Methods: We studied 44 patients with HOCM and coronary artery disease (CAD) who underwent septal myectomy and CABG) between 2011 and 2017. The control group was matched in a ratio of 4:1 based on age, sex, body mass index, hypertension, and chest pain. Results: Compared to patients without CAD, patients with CAD had a higher long‐term cardiovascular mortality rate (0.6% vs 6.8%, P = 0.03; hazard ratio [HR] = 8.16, 95% confidence interval [CI]: 1.27‐74.48, P = 0.03). In addition, 10 out of 176 (5.7%) patients without CAD and nine out of 44 (20.5%) patients with CAD achieved the secondary endpoints (progressive heart failure, unexplained syncope, stroke, atrial fibrillation, and myocardial infarction) (HR = 2.89, 95%CI: 1.03‐8.12, P = 0.04). The 5‐year survival rate and cardiovascular event‐free survival rate were significantly higher in patients without CAD than in those with CAD (97.4% vs 93.9%, P = 0.03; 89.2% vs 80.1%; P = 0.04). In the multivariate analysis, presence of CAD, New York Heart Association class, and left atrial diameter were predictors of combined cardiovascular events when adjusted for age and male sex. Conclusions: The cardiovascular death and cardiovascular events are significantly increased in patients with HOCM and CAD who underwent CABG at the time of septal myectomy.